THE EFFECT OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITY, SHARIAH COMPLIANCE, COMPANY SIZE AND SHARIA SUPERVISORY BOARD ON PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Krisnawati, Yuni (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study was to find out and analyze the influence of Islamic corporate social responsibility, shariah compliance, company size and the shariah supervisory board partially and simultaneously on the profitability of sharia commercial banks in Indonesia. The population of this research is as many as 13 sharia commercial banks in Indonesia with 2011 to 2017 observation years. Samples were selected using saturated sample method. Data is processed using panel data regression statistical test methods. The results of this study prove that Islamic corporate social responsibility, Islamic income ratio and company size partially have a positive and significant effect on profitability at Islamic commercial banks in Indonesia. While the profit sharing ratio, zakat performance ratio and sharia supervisory board have a positive and not significant effect on profitability in sharia commercial banks in Indonesia. Simultaneously Islamic corporate social responsibility, Islamic income ratio, profit sharing ratio, zakat performance ratio, company size and sharia supervisory board have a significant effect on profitability in Islamic commercial banks in Indonesia.